2016
DOI: 10.1002/ccd.26718
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of SMART stent implantation in patients with femoro‐popliteal disease

Abstract: Although SMART stent implantation produced favorable long-term results, TASC IIC/D FP lesions had poor outcomes. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In terms of postoperative patency, the primary patency was significantly longer in the patients of the group with occlusion lesions <2 cm compared with the group with occlusion lesions ≥ 2 cm ( Figure 9C ). There are no relevant data in the endovascular treatment of CVO/CVS before, while a negative correlation between lesion length and postoperative patency has been documented in the field of arterial interventions ( 19 , 20 ). Many previous studies have suggested that calcification or organization is one of the main causes of recanalization failure ( 13 , 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of postoperative patency, the primary patency was significantly longer in the patients of the group with occlusion lesions <2 cm compared with the group with occlusion lesions ≥ 2 cm ( Figure 9C ). There are no relevant data in the endovascular treatment of CVO/CVS before, while a negative correlation between lesion length and postoperative patency has been documented in the field of arterial interventions ( 19 , 20 ). Many previous studies have suggested that calcification or organization is one of the main causes of recanalization failure ( 13 , 21 23 ).…”
Section: Discussionmentioning
confidence: 99%